Pembentukan Karakter pada Anak Usia Dini melalui Program Toilet Training - Novan Ardy Wiyani; Mukhtar Nurkamelia (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
Character building is very appropriate to be carried out from an early age in the implementation of education that focuses on character building. However, not all educational institutions are able to organize various character building programs for children. Toilet training is one of the programs that can be done to shape children's character. This paper is intended to describe and analyze the process of character building for children through the toilet training program at PAUD Abaca. The data in this study were collected through interviews, observation and documentation. Then the data was analyzed using the stages of data reduction, data display, and verification. The results showed that there were three stages carried out by the teacher in the implementation of the toilet training program to shape the child's character, namely the stage of introducing kindness, the stage of doing kindness and the stage of reviewing kindness. The result of the toilet training program is that children have the ability to be obedient to the rules and etiquette of washing. This obedience makes children able to be disciplined, independent, responsible and love cleanliness when washing in the toilet.